Development of Academic Supervision Based on the TIRTA-Innovative Coaching Flow to Improve Teachers' Professional Competence - Handayani, Mugih; Hartinah, Sitti; Nafiati, Dewi Amaliah (Journal of English Language and Education, 2025)
This research in the form of developing academic supervision based on TIRTA-Innovative Coaching flow as an innovative approach in academic supervision aims to 1) Describe the condition of TIRTA-Innovative coaching-based academic supervision that is currently applied in improving teachers' professional competence; 2) Develop a development model of TIRTA-Innovative coaching-based academic supervision; 3) Test the effectiveness of the model in improving teachers' professional competence; 4) Identify the TIRTA-Innovative coaching-based academic supervision model in improving the professional competence of elementary school teachers in Dabin Dr. Wahidin Sudiro Husodo; 5) Describe the TIRTA-Innovative coaching-based academic supervision framework model. This research method involves a qualitative approach with a design using library research by using studies related to various writings, both in the form of books, journals, articles, and other appropriate sources, as well as analyzing documents related to academic supervision. This research makes a significant contribution to the development of TIRTA-Innovative flow coaching-based academic supervision. The findings can provide practical guidance for education practitioners, principals, and policy developers in improving teachers' professional competence.